Mushalla Management Strategy in Building Tolerant Values with Non-Muslim Communities (Study at the Raudhatul Jannah Prayer Room, Lubuk Kilangan District, Padang City) - Putra, Ahmad; Siregar, Rian Syaputra; Rosdialena; Husnul Hifzhi (Al-Wasatiyah: Journal of Religious Moderation, 2024)
This research was motivated by complaints and protests from non-Muslim residents to the Raudhatul Jannah Mushalla Management, Padang City in the holy month of Ramadan. This protest was not without reason, but was focused on the Ramadan study material presented by the speaker at the prayer room. Some materials containing intolerance were one of the reasons why people around the Mushalla who were not Muslims protested and expressed their complaints. This research uses qualitative methods, strengthened by conducting observations and interviews with parties who are considered capable of answering the problems that the author is studying. The results of this research show that: first, the administrators asked the ustadz or Ramadan lecturers to deliver material that does not offend non-Muslims, second, the prayer room administrators began planning to regulate the title of Ramadan lectures for each lecturer during the holy month of Ramadan, third, the administrators and staff always appeal to the entire community to continue to respect differences in creeds, fourth, administrators regulate the volume of prayer rooms so as not to disturb the peace of non-Muslim communities.